Розробка внутрішньопрограмної системи контролю версій - Зуєвський, Д. Р. (ХНУРЕ, 2023)
The work considers the task of automatic storage of individual entities versions within developed software application. It is suggested to use an addon that automatically creates a duplicate of a single changeable object in application, and will update this duplicate instead of updating the version of entire application. The approach ensures independence of versions, minimizing time for creating iterations.
Keywords: система контролю версій